IFactor Determinants of Timeliness of Financial Reporting inILQ45 Companies in Indonesia - Rosita, Rika; Sundarta, M. Imam; Azis, Azolla Degita (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2023)
The aim of this study is to earn knowledge about the effect of profitability, firm age, and firm size on the timeliness of financial reporting. This study population is made up of companies listed on the BEI (Indonesia Stock Exchange) that are included in the LQ45 index, which consists of 45 companies for the 2018–2021 period. Sample selection used the purposive sampling method and obtained 100 samples from 25 companies. Collecting data for this study using the documentation Method Hypothesis testing was carried out using the logistic regression analysis method using the IBM SPSS 24 program at a significance level of 5%. The results of the study show that the profitability and company size variable has no effect on the timeliness of financial reporting meanwhile company age has a negative effect on the timeliness of submitting financial reports for LQ45 companies on the IDX with the observation years 2018, 2019, 2020, and 2021.